2023
DOI: 10.1039/d2ra05368c
|View full text |Cite
|
Sign up to set email alerts
|

Schwann cell-matrix coated PCL-MWCNT multifunctional nanofibrous scaffolds for neural regeneration

Abstract: Schwann cell-derived matrix coated scaffolds for peripheral nerve regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 52 publications
2
11
0
2
Order By: Relevance
“…Such disruption by filler particles also disrupts intrinsic movement of polymer chains and their organization within a scaffold which can lead to a reduction in the stretchability of the scaffolds as observed here. The observed reduction in elongation at break of polymer matrices (films, scaffolds) are in agreement with previously reported studies [ 41 , 53 – 56 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Such disruption by filler particles also disrupts intrinsic movement of polymer chains and their organization within a scaffold which can lead to a reduction in the stretchability of the scaffolds as observed here. The observed reduction in elongation at break of polymer matrices (films, scaffolds) are in agreement with previously reported studies [ 41 , 53 – 56 ].…”
Section: Discussionsupporting
confidence: 93%
“…We have previously demonstrated that Schwann cells also secrete extracellular matrix which helped to provide biochemical cues to improve cell proliferation and adhesion on the PCL nanofibrous scaffolds [ 24 ]. In another work, we also confirmed that Schwann cell acellular matrix when coated on PCL and multiwalled carbon nanotube scaffolds showed a significant expression of peripheral myelin protein 22 (PMP22) gene [ 41 ]. Based on these results, we deduced that Schwann cell matrix in combination with PCL scaffolds could promote more functional neuronal properties such as myelination.…”
Section: Introductionmentioning
confidence: 71%
“…Manasa Nune et al [ 45 ] have proved that self-assembling peptide nanostructures on aligned PLGA nanofibers can provide better cell–matrix communication and stimulate nerve remyelination. Other study indicates that uniaxially oriented fibers could guide migration of SCs but surface properties of scaffolds may be more influential than scaffold morphology in nerve regeneration [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The integration of 3D printing technology in tissue engineering has revolutionized the creation of functional and implantable tissue constructs. Additive manufacturing techniques are employed to fabricate biomaterial scaffolds with patient-specific geometries and porous networks that facilitate tissue growth. , Traditional methods involve fabricating the scaffolds first and then incorporating the cells, which can result in a non-uniform cell distribution. However, the emerging field of bioprinting allows for the simultaneous printing of cells and biomaterials, enabling precise cell placement within the printed tissues . Bioprinting techniques can be categorized as vat polymerization, material extrusion, or material jetting. Vat polymerization-based printing involves the fabrication of scaffolds, onto which cell seeding is usually carried out.…”
Section: Introductionmentioning
confidence: 99%